Vacuum-packaged ground beef: the influence of color and educational materials on consumer acceptance - Lynch, N.M.; Kropf, Donald H.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Questionnaires were completed by 1750 Kansas grocery shoppers in selected Dillon's supermarkets to determine how product color and educational materials affected their purchase intent of vacuum-packaged ground beef. Half the consumers received educational materials (informed consumers). Informed consumers were more likely (P<.0001) to indicate a positive purchase intent for vacuum-packaged ground beef than uninformed consumers. Informed consumers were as likely to purchase the purple-red, vacuum-packaged product as the bright cherry-red product to which they are accustomed. Product color was important in their product purchase decision. Vacuum-packaged ground beef should compete favorably with the conventionally packaged product, if educational materials are provided to explain the color differences.
Keywords: Beef; Ground beef; Color